Impacts of body positions on the geniohyoid muscle contraction and swallowing difficulty in healthy adults - Fuwen Lu; Tatsuma Okazaki; Junko Okuyama; Shin‐Ichi Izumi (Wiley, 2023)
Abstract Background Body positions affect swallowing and gastroesophageal reflux. Swallowing impairment is one of the main causes of aspiration pneumonia. To prevent pneumonia, evaluation of body positions on gastroesophageal reflux recommended 30 degrees or higher semi‐recumbent positions. The geniohypoid muscle and tongue play central roles in swallowing. However, the effects of body positions on contracting rates in the geniohyoid muscle and tongue pressure are unclear. Moreover, correlations between geniohyoid muscle contracting rates and subjective swallowing difficulties are unclear. Aims This study aimed to identify the proper body positions on contracting rates in the geniohyoid muscle, tongue pressure, and subjective swallowing difficulties. Materials & Methods Twenty healthy adults swallowed 15‐ or 50 ml of water at 90 degrees sitting, 60‐ and 30 degrees semi‐recumbent, and 0 degrees supine positions. We scored the subjective swallowing difficulties and measured the tongue pressure and the number of swallows. An ultrasound evaluated the geniohyoid muscle size and contracting rates. Results At sitting and 60 degrees semi‐recumbent positions, the geniohyoid muscle showed greter contracting rates than at 30 degrees semi‐recumbent and supine postions (P < 0.05), which resulted in easier swalloiwng. Greater tongue pressure was weakly correlated with fewer swallows (r = ‐0.339, P = 0.002), whereas the body positions did not affect. Conclusion Considering swallowing and gastroesophageal reflux together, a trunk angle of 60 degrees or more might be beneficial for reducing the risk of aspiration.